Investigation of the presence of heavy metals, total coliform bacteria, minerals and water hardness in tap water and water cooler water of five faculties in UiTM, Shah Alam. / Khairusy Syakirah Zulkifli - Zulkifli, Khairusy Syakirah (Faculty of Applied Sciences, 2009)
Water is very important for human and despite its importance; water is one of the poorly managed resources on earth. The effect of water pollution is harmful to every living and can disrupted humans' activities and health. By performing this research, the quality of water in UiTM can be determined. Samples from two different sources which are tap water and water cooler water was taken from five selected faculties in UiTM. Every sample was tested for the presence of heavy metals, minerals using the ICP-OES. Water samples were also tested for bacteria presence using the Membrane Filtration Method with M-Endo Agar. The results obtained were then compared with Malaysian Ministry of Health water quality standards for drinking water. The analysis of total heavy metal concentrations indicated that there is great variation of concentration of different metals in different water types. Most water samples had iron concentration above acceptable value however, nickel and zinc concentration are relatively low. The presence of bacteria and the water minerals in water samples are also low. The both tap and water cooler water also had water hardness between 30-40 CaC03 mg/L, and thus is classified as soft water. From the study, it can be concluded that water from tap is much cleaner and safer than water from water cooler in terms of total coliform bacteria and presence of heavy metals..